Institutional Components Affecting the Internationalization of Higher Education: A Case Study on Estonia - Joamets Kristi; Vasquez Maria Claudia Solarte (Baltic Journal of Law & Politics)
A comprehensive understanding of higher education internationalization remains elusive within the European context, despite the guidance offered by the European Union (EU) through policy principles, notably the Bologna Process. As a result, Member States face challenges in developing and implementing effective internationalization strategies. Typically, these prove unsustainable due to their overly ambitious and broad focus, leading to inefficiencies such as inadequate allocation of resources, and to fragmented approaches that often fail to produce cohesive, functional systems. This paper argues that establishing clear definitions, priorities and coordinated action plans involving key stakeholders could enhance the formulation of more feasible and impactful regulatory strategies, facilitating a smooth internationalization in the European Higher Education Area (EHEA). The opposite would increase the likelihood of wasteful investments and mismanagement, affecting the stability, reliability, and sustainability of advancements in this area. This article contributes to the delineation of a higher education internationalization model drawing from an examination of Estonian institutional policies and regulatory trends. Through a partial institutional review, it explores the challenges, opportunities, and prospects inherent to cultiva ting a well defined, principled and comprehensive internationalization approach, emphasizing the necessity of meaningful stakeholder involvement for the creation of reflective regulatory frameworks to ensure the attainment of tangible and measurable goals.